Doing European ethnology in a time of change - Johler, Reinhard (Traditiones (Ljubljana), 2012)
Sciences change and develop, but rare are the disciplines that experience such shifts in paradigm as is the case in ethnology, Volkskunde, in German-speaking countries. This is linked to its history (and its involvement in national socialism), but it is also possible to explain with the profound changes of the research field - from a peasant society to the globalized everyday of the 21st century. We may ask ourselves, if in this regard the "special German path", "German Sonderweg" has come to its end or if the discipline - together with its national sister discipline such as European ethnology is moving towards a common European future. This piece represents an attempt to shed light on the problems as well as possibilities of such a project. In any case Slovenian ethnology also has an important role in this endeavor.
Keywords: ethnology; Etnologija; European ethnology; Evropska etnologija; history of ethnology; Zgodovina etnologije; Evropa; Europe; zgodovinski pregledi